Attitude of Patients towards the Presence of Medical Students during Consultations - Ali, Iyad; Shaar, Aida; Aker, Salam (Jordan Medical Journal, 2019)
Background and Aims: Bedside teaching is seen as one of the most important component of medical education. A balance must be found between the best management of the patient and the education process. This study aims to determine patients’ attitudes toward the presence of medical students during consultations in the newly established teaching hospital in Palestine. The factors that affect the patients’ attitude were determined in order to provide valuable information to medical tutors to plan future clerkships in a way that maximize patients comfort and improve teaching process. Materials and Methods: This cross-sectional study was conducted at An-Najah National University Hospital. It is based on a self-administered questionnaire from patients in the waiting rooms of different clinics. Four hundred and five questionnaires were collected between September 2015 and August 2016. Results: About 64.8% of patients didn’t mind the presence of medical students during consultations and 72.4% were ready to allow students to examine them under supervision. The vast majority of patients (about 90%) reported that they understand the importance of interaction of medical students with patients during their clinical education. Considering the number of students that patients will feel comfortable in their presence, 63.7% of patients preferred one or two medical students to be present during consultation Conclusions: This study showed an overall positive patients’ attitudes to the medical students’ involvement in the medical consultation. However, it is essential that ethical conduct and professionalism are maintained to guarantee optimal care and safety to patients and good medical education to future physicians.